Revitalisasi Pendidikan Akhlak Nabawi sebagai Strategi Penguatan Resiliensi Keluarga Muslim Peri-Urban di Era Digital - Ratna Suraiya; Moch. Zakki Mubarok; Nashrun Jauhari; Fathul Chodir; Mohamad Dahlan (Yayasan Literasi Altruis Khatulistiwa, 2025)
This Community Service Program is designed to revive Nabawi moral education within peri-urban Muslim families through a participatory service learning approach. The main focus of the program is to strengthen family resilience amidst the wave of digitalization that brings various social and spiritual challenges. The partner community, the congregation of Musholla Al-Fattah in Prasung Village, Sidoarjo, faces issues such as declining face-to-face interaction, increasing individualistic attitudes, weak parental supervision over gadget use, reduced attention to worship and morality, as well as the threat of children and adolescents becoming involved in online gambling practices. The program was carried out through five main stages: identifying family resilience needs, conducting interactive thematic studies of the Sirah Nabawiyah, collective reflection, participatory evaluation, and celebrating the learning outcomes. The core product was the internalization of moral values through the study of the Sirah Nabawi, with emphasis on the principles of ṣidq (honesty), amānah (responsibility), ḥilm (patience), raḥmah (compassion), and istiqāmah (consistency). The study was structured in an applicative manner and tailored to the local family context of the congregation. The results of the program demonstrated the emergence of family awareness regarding spiritual and social roles, strengthened communication among family members, and active involvement of the congregation in moral education. This PKM highlights the urgency of Nabawi-based moral education as the foundation of family resilience in peri-urban Muslim communities, while also recommending the development of similar studies that are adaptive, reflective, and sustainable in other communities with comparable dynamics.